Discovery of a hidden form of neuropeptide F and its presence throughout the CNS–gut axis in the mud crab, Scylla olivacea - Kruangkum, Thanapong; Duangprom, Supawadee; Songkoomkrong, Sineenart; Chotwiwatthanakun, Charoonroj; Vanichviriyakit, Rapeepun; Sobhon, Prasert; Kornthong, Napamanee (Frontiers in Marine Science, 2022)
The mud crab Scylla olivacea (Scyol) is an economically crucial crustacean species in Thailand, due to its high market demand and nutritional value. The neuropeptide F (NPF) has been implicated in the coordinated regulation of feeding and metabolism in invertebrates. While various isoforms of neuropeptide F (NPF) have been previously explored in the mud crab, some knowledge gaps in relation to the NPF family, and ambiguities in the nomenclature from previous reports, remain. In this study, NPF was firstly localized in the central nervous system and gastrointestinal tract of the mud crab, S. olivacea, using a polyclonal antibody against Macrobrachium rosenbergii, Macro-NPF. The NPF immunoreactivity (ir) was detected dominantly in the X-organ/sinus gland complex of the eyestalk (ES) and the various neuronal clusters (cluster 6, 9/11, and 14/15) and neuropils (anteromedial and posteromedial protocerebral neuropils, olfactory and accessory olfactory neuropils, and medial antennule neuropil, columnar neuropil) of the brain (BR), commissural ganglia, and suboesophageal ganglion of the ventral nerve cord (VNC). Interestingly, this study also presented the NPF immunoreactivity (NPF-ir) in the acinar gland-like cell and spindle-shaped epithelial cells of S. olivacea intestine. The full-length Scyol-NPFII was characterized by molecular cloning and revealed 414 nucleotides with 375 nucleotides of an open reading frame which encoded 124 deduced amino acids. A 124-amino acid precursor protein of Scyol-NPFII included a 26-residue signal peptide and a 69-amino acid mature peptide. The Scyol-NPFII showed the highest percentage of hit similarity to S. paramamosain-NPFII and clustered in the NPFII family, separated from the other forms of NPFs in this species. The spatial gene expression in various tissues revealed that Scyol-NPFII was found dominantly in the ES and BR, VNC, heart, intestine, and muscle. This study provided a novel form of NPF in the female mud crab, S. olivacea, which could open the possibility of its functioning in the brain-to-gut controlling axis. This study could provide essential information for further application in the cultured system of S. olivacea in the near future.